Changes of maximal power output of lower extremity during a decathlon - Edouard, P.; Morin, J.-B.; Samozino, P. (British Journal of Sports Medicine, 2014)
Background: In decathlon, a higher injury risk over other Athletics disciplines has been reported. It may be caused by neuromuscular fatigue, which may be induced by repeated maximal efforts over the two days of competition. Objectives: To determine the change in lower extremity power output over the course of a decathlon in order to better define/understand 1) the functional demands represented by decathlon, 2) the muscular mechanical capabilities determining decathlon performance, and 3) their potential relationships with injury risk factors. Design: Cross-sectional controlled study. Setting: Field conditions during the 2010 French National Decathlon Championships.Participants 6 national-level athletes and 11 representative control subjects.Main outcome measures The change in lower extremity power output, and its force and velocity components, was tested on the basis of maximal squat jump and cycling sprint measurements, at the beginning and end of the two days of competition. Results: No differences in squat jump and cycling sprint values were found between each testing time (P>.05), while significant lower squat jump values for control participants were reported at the second day beginning (P<.05). Conclusions: No significant changes in lower extremity muscle power output were reported over the course of a decathlon, suggesting no substantial neuromuscular fatigue was induced by two days of decathlon competition. We can therefore reasonably assume that the accumulation of fatigue (and/or neuromuscular fatigue, if any) does not play a major role in injury risk in decathlon. Higher injury risk reported in decathlon may be due to the sum of the injury risks of the 10 events. Our study could be considered as a pilot study, and future studies should be done to confirm these preliminary results.